2018
DOI: 10.1111/nep.13160
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of biopsy proven renal disease in South Asian children: Two decades at a tropical tertiary care centre

Abstract: This study provides the largest data on biopsy proven renal disease in children from South Asia published till date and highlights important differences in the spectrum and trends of kidney disease compared to data from other regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
4
7
3
1
Order By: Relevance
“…The mean age at biopsy was about 10 years, which is corresponding to results reported in other countries [7-9, 11, 18, 22, 31]. However, sometimes that mean age was higher [15,16] or lower [13,[28][29][30]32].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The mean age at biopsy was about 10 years, which is corresponding to results reported in other countries [7-9, 11, 18, 22, 31]. However, sometimes that mean age was higher [15,16] or lower [13,[28][29][30]32].…”
Section: Discussionsupporting
confidence: 70%
“…In our study, acute renal failure was a less important reason for renal biopsy, while some studies reported similar [7,9,11,37], higher (10.7-17.5%) [2,10,18,20], or lower numbers (1.4-4.4%) [8,15]. Similarly, chronic renal failure, was also less important reason for renal biopsy in our research.…”
Section: Indications For Renal Biopsycontrasting
confidence: 39%
See 3 more Smart Citations